ANALISIS KINERJA SIMPANG APILL BERDASARKAN PKJI 2014 DIBANDINGKAN SOFTWARE PTV VISTRO: ANALISIS KINERJA SIMPANG APILL BERDASARKAN PKJI 2014 DIBANDINGKAN SOFTWARE PTV VISTRO - Rikki Sofyan Rizal; Eko Wiyono; Rangga Danisworo (Universitas Widyatama, 2022)
Analyzing the characteristic and causes of congestion in cities is the initial capital in order to determine traffic policies and appropriate management plans. One of the locations of congestion that needs to be reviewed is the intersection, because it is a meeting point of various movements from different directions. This research was conducted to analyze the performance of Simpang Empat Legundi using the PKJI 2014 method and then compared to PTV Vistro. The research began with the collection of both primary and secondary data to meet the intersection performance parameters of the store in PKJI (2014) and PTV Vistro. A comparison of the two methods is done to analyze different parameters in the analysis of the intersection performance. The results of the analysis on PKJI (2014) obtained a degree of saturation of 0.967 and a delay of 99.76 det / skr while at PTV Vistro showed a degree of saturation of 0.984 and a delay of 241.19 det / skr. The results of the analysis of both methods show the equation OF L with delay >80 det / skr Difference in value occurs due to PTV Vistro Data analysis to determine capacity, saturation degree, and delay analyzed with HCM 2010. Input values that are not in accordance with PKJI (2014) also affect the difference in the results of the analysis, including the direction of vehicle movement is not in accordance with the storage conditions, environmental conditions are considered the same every lane group i.e. CBD, and the saturated current value (S0) of 3600 which is considered the same in each lane group. Keywords : Intersection Performance; Parameters; PKJI 2014; PTV Vistro.